Hukum Responsif dan Penegakan Hukum di Indonesia (Lex Jurnalica, 2010)
AbstractExisting law in Indonesia is still largely dominated by the Dutch colonial legal heritage through its products are now valid with various modifications, equipped with new laws to regulate the newly emerging field later. There is no denying that in the colonial period, the law is not used in a positive function, in the sense of being used for the purpose of the law itself that is to give justice but more accurately described as a colonial tool to strengthen its position and gain legitimacy in punishing the freedom fighters. Law became a sub system of the colonial system so that the law does not have autonomy. In this study the authors want to discuss about how responsive the legal relationship with law enforcement in Indonesia? The purpose of this study was to determine the relationship in the context of responsive law enforcement in Indonesia. The results of this study is expected to bring usability or theoretical contribution in terms of thinking; as a contribution to thought and effort to develop the science of law, particularly relating to the State Administration Law, Philosophy of Law, Legal Theory and Legal Politics. Practical Aspects; research is expected to contribute ideas and information to the general public about the philosophy of jurisprudence and the theory of science, especially in the field of administrative law and politics. The method used in conducting this research is normative juridical approach which focuses on the research literature or data is called secondary dataKeywords: Responsive law, Enforce, Indonesia